Tindak Pidana Pemalsuan Ijazah Dalam Perspektif Kuhp Dan Undang-Undang Sistem Pendidikan Nasional - Sari, Linda; Siswanto, Heni; Muhtadi, Muhtadi; Fardiansyah, Ahmad Irzal; Rosidah, Nikmah; Firmansyah, Ade Arif (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2025)
Forgery of diplomas is a criminal offense that not only damages the integrity of the education system, but also threatens public trust in educational institutions and government. Although diploma forgery has been regulated, the practice of forgery still occurs frequently due to the lack of synchronization between the two regulations. This research aims to analyze the relevance and synchronization between the Criminal Code and the National Education System Law in handling the criminal act of diploma forgery so as to provide a comprehensive understanding of more effective law enforcement. The method used is normative- juridical research with statute approach and conceptual approach. Data is sourced from primary legal materials in the form of provisions in the Criminal Code and the National Education System Law, as well as secondary legal materials such as journals, legal literature, and related court decisions, namely district court decision Number 43/Pid.B/2021/Pn. Liw and the analysis is done descriptively-qualitatively. The results show that the regulation of diploma forgery in the Criminal Code is still general in nature through Article 263 on forgery of letters, while the National Education System Law only emphasizes administrative aspects without clear regulation of criminal sanctions. This has led to dualism in the application of the law and the potential for a legal vacuum in practice